THE RELATIONSHIP BETWEEN STUDENT KNOWLEDGE AND ATTITUDES AND BSE BEHAVIOR (BREAST SELF-EXAMINATION) AT THE FACULTY OF PUBLIC HEALTH, ISLAMIC UNIVERSITY OF NORTH SUMATERA UTARA - Apriadi Siregar, Putra; Tumanggor, Suro Rahmadhona (Pena Cendekia Insani, 2025)
The Cancer is the leading cause of death in the world after cardiovascular disease. Breast cancer represents 1 in 4 cancers diagnosed among women globally. This cancer ranks first in terms of the highest number of cancers in Indonesia and is one of the first causes of death from cancer. This study aims to determine the relationship between knowledge and attitudes of students with BSE (Breast Self-Examination) behavior at Faculty of Public Health, Islamic University of North Sumatera Utara. This study uses a quantitative descriptive correlational research with a cross-sectional approach. The population in this study were all female students of the Public Health Study Program at Islamic University of North Sumatra with a sample of 55 respondents. The data collected was processed manually and then analyzed bivariately and univariately using SPSS 20 (Statistical Program for Social Sciences 20). From the results of the study it was found that students with sufficient knowledge were 26 people (47.3%) and more had a negative attitude were 39 people (70.9%). Most of the female students of Faculty of Public Health, Islamic University of North Sumatra had unsupportive behavior were 42 people (76.4%). There is no significant relationship between knowledge and BSE behavior where the value is p>0.05 (0.578), but there is a significant relationship between attitudes and BSE behavior where the value is p<0.05 (0.025).